SAFETY OF HIGH INTENSITY ACCELERATED CORNEAL COLLAGEN CROSS-LINKING IN KERATOCONUS PATIENTS ON BASIS OF ENDOTHELIAL CELL DENISITY - Fida, Abida; Humayun, Sadia; Fatima, Iram; Basit, Imran; Ishaq, Mazhar; Hussain, Fida (Journal of Ayub Medical College Abbottabad, 2018)
Background: This study was conducted to evaluate the safety of accelerated corneal collagen crosslinking (CXL) in keratoconus patients on basis of endothelial cell density measurements. Methods: We studied 24 patients (42 eyes) with diagnosed keratoconus who underwent accelerated CXL with 9 Mw/cm2 UVA irradiance for 10minutes. All patients underwent detailed examination and video keratography (VKG) for classification and confirmation of keratoconus. Patients with central corneal thickness (CCT) of ‰¥400µ were included in the study. Specular microscopy was done to note endothelial cell density (ECD) preoperatively and then at the end of 1st, 4th and 12th weeks' post-operative period. Results: The study included 24 patients (42 eyes) from October 2016 to June 2017. Among these 13 were females and 11 males with mean age of 20.15±6.73 years. Eighteen patients underwent the procedure in both eyes while 6 had the procedure in one eye. The pre-operative ECD mean±SD of right eye was 2743.97±542.77/mm2 and left eye was 2763.35±532.57/mm2. The post-operative ECD mean±SD of right and left eyes at the end of 12th post-op weak were 2806.34±520.11/mm2 and 2823.30±628.57/mm2 respectively. The pre and post-op ECD comparison showed p-values at first week post-op are 0.474 and 0.683 for right and left eyes respectively. Similarly, the p-values at 4th and 12 weeks post-op for right eye are 0.266 and 0.280 respectively. The p-values at 4th and 12th weeks for left eye are 0.913 and 0.404 respectively. Conclusion: Accelerated CXL protocols is safe and effective procedure and did not lead to significant change in ECD in our study population in three months post-procedural follow up. However further research is required to determine the effect of high intensity UVA radiation on other ocular structures with larger group of patients and long-term follow up. Keywords: Keratoconus; Prevalence; Epithelium-off corneal crosslinking